Sosialisasi dan Pelatihan Komputer di SDN 015 Pasir Keranji - Fauza, Naila; Samudera, Amelia Putri Disar; Tsania, Delvani Tri; Ihsan, Dzikry Muhammad; Darpiza, Gustina; Mulya, Ikhsan Hadi; Wati, Rahma; Sentosa, Ridho Wahyu; Ramadhani, Syania Eka; Satifa, Yoriza; Hunafa, Zartasya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The ability in Information and Communication Technology or ICT is very much needed nowadays because of the increasing modernization in almost all aspects of life. This ability is also very much needed even since elementary school age. In the education system in Indonesia, there is an assessment program, namely ANBK. This program is intended for students in grade 5 at elementary school level, grade 8 at junior high school level, and grade 11 at high school/vocational school level. One of the schools that participated in this ANBK program is SDN 015 Pasir Keranji which is located in Pasir Penyu District, Indragiri Hulu Regency, Riau Province. However, there is a problem, namely the lack of knowledge of students at SDN 015 Pasir Keranji regarding the use of computers. Therefore, as a form of community service, KUKERTA Students of Riau University carried out socialization and training in the use of computers for students at SDN 015 Pasir Keranji, especially for students in grade 5. This training includes training in the use of word processing applications, namely Microsoft Word, as well as training in filling out online forms as well as simulations of the implementation of ANBK, namely using Google Form media. This training is expected to provide knowledge and skills to students of SDN 015 Pasir Keranji in using computers, especially as preparation for facing the ANBK program.